2019
DOI: 10.1017/brimp.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the experiences and needs of deep brain stimulation for people with Parkinson’s disease and their family members

Abstract: BackgroundDeep brain stimulation (DBS) is an effective treatment for the motor symptoms of Parkinson’s disease (PD). The lived experience of people with PD suggests a process of adjustment follows. This study aimed to explore the adjustment and associated education and support needs of people with PD undergoing DBS and their family members across the continuum of the DBS experience.MethodA structured qualitative description study including semi-structured interviews with people with PD (n = 14), family members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…There are limitations to contractual “disclose and sign” informed consent processes, notably that information presented preoperatively is later forgotten or goes unappreciated. There have been recommendations for more experiential and interactive forms of informed consent in DBS ( Bell et al, 2010 ; Liddle et al, 2019 ), that draw upon the knowledge of lived experience experts. Such a process could involve corrective feedback and use of narrative accounts from DBS recipients and their families (e.g., videos, written accounts).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limitations to contractual “disclose and sign” informed consent processes, notably that information presented preoperatively is later forgotten or goes unappreciated. There have been recommendations for more experiential and interactive forms of informed consent in DBS ( Bell et al, 2010 ; Liddle et al, 2019 ), that draw upon the knowledge of lived experience experts. Such a process could involve corrective feedback and use of narrative accounts from DBS recipients and their families (e.g., videos, written accounts).…”
Section: Discussionmentioning
confidence: 99%
“…As such, informed consent for this long-term and adaptable neurotechnology requires an iterative and ongoing process. This recommendation has previously been made for DBS in Parkinson’s disease ( Kubu et al, 2018 ; Liddle et al, 2019 ; Mosley et al, 2019 ), and is potentially more relevant in clinical trials of DBS for psychiatric conditions where the risks and benefits are less established.…”
Section: Discussionmentioning
confidence: 99%
“…Direct education from clinicians to patients and caregivers does not guarantee information is retained or ensure preparedness to manage changes (Mosley et al, 2019). More experiential information that uses the words and language of other PD patients and families has been suggested for improving comprehension and setting realistic expectations (Liddle et al, 2019). Our interviews demonstrated personal experiences from other DBS patients and families were well retained by participants and influential in establishing their expectations.…”
Section: Discussionmentioning
confidence: 99%
“…These included the stimulation adjustment process, development of new symptoms and the impact of changes, both positive and negative, on relationships and roles (Haahr et al, 2010). A more recent exploration of DBS experiences of people with Parkinson's indicated that particular education, clinical and support needs were experienced at different times (Liddle, Beazley, Gustafsson, & Silburn, 2019). Timely clinical support may be required to support adjustment and participation in meaningful occupations (Liddle et al, 2018(Liddle et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent exploration of DBS experiences of people with Parkinson's indicated that particular education, clinical and support needs were experienced at different times (Liddle, Beazley, Gustafsson, & Silburn, 2019). Timely clinical support may be required to support adjustment and participation in meaningful occupations (Liddle et al, 2018(Liddle et al, , 2019. The recovery period after DBS is a key transition time requiring a focus on occupational participation, health and wellbeing outcomes.…”
Section: Introductionmentioning
confidence: 99%